Aquaculture engineering (Elsevier Applied Science, 1996)
Aquaculture engineering requires knowledge of the many general aspects of engineering such as material technology, building design and construction, mechanical engineering and environmental engineering. In this comprehensive book, Odd-Ivar Lekang introduces these principles and demonstrates how such technical knowledge can be applied to aquaculture systems, offering the reader coverage including: